SISTEM INFORMASI KOMITE OLAHRAGA NASIONAL INDONESIA (KONI) PROVINSI JAMBI - Kodri, Kodri; Mulyati, Sri; Adriana, Windy (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2024)
The Indonesian National Sports Committee (KONI) of Jambi Province is an organization responsible for nurturing athletes from Jambi Province, currently overseeing approximately 7,000 athletes. Athlete data is currently managed by KONI at the district or city level, making it challenging to identify the potential talents among the athletes. Therefore, this research aims to develop a web-based information system. The system is built using the Waterfall methodology, consisting of five planning stages: needs analysis, system design, implementation, system testing, and maintenance. During development, the system utilizes PHP programming language with the Laravel Framework and MySQL as the database. Feature testing conducted on the system demonstrates that each feature functions effectively. In conclusion, this research finds that the system can be utilized effectively.